A Diagnostic Solution for Lupus Anticoagulant Testing in Patients Taking Direct Oral FXa Inhibitors Using DOAC Filter - Farkh, Carine; Ellouze, Syrine; Gounelle, Louis; Sad Houari, Mama; Duchemin, Jérôme; Proulle, Valérie; Fontenay, Michaela; Delavenne, Xavier; Jourdi, Georges (Frontiers in Medicine, 2021)
Direct oral factor Xa (FXa) inhibitors interfere with Lupus Anticoagulant (LA) assays challenging antiphospholipid syndrome diagnosis in treated patients. We evaluated a new device, called DOAC Filter, usefulness in this setting. It is a single-use filtration cartridge in which FXa inhibitor compounds are trapped by noncovalent binding while plasma is filtered through a solid phase. Patient samples were analyzed before and after filtration: 38 rivaroxaban, 41 apixaban and 68 none. Anticoagulant plasma concentrations were measured using specific anti-Xa assays and HPLC-MS/MS. LA testing was performed using dilute Russell Viper Venom Time (dRVVT) and Silica Clotting Time (SCT). Baseline median [min‐max] concentrations were 64.8 [17.6; 311.4] for rivaroxaban and 92.1ng/mL [37.1; 390.7] for apixaban (HPLC-MS/MS). They were significantly correlated with anti-Xa assays results (r=0.98 and r=0.94, respectively). dRVVT was positive in 92% rivaroxaban and 72% apixaban and SCT in 28 and 41% of samples, respectively. Post-filtration, median % of neutralization was 100% with rivaroxaban and apixaban concentrations of respectively <2 [<2‐2.4] and <2ng/mL [<2‐9.6] using HPLC-MS/MS. No significant effect of DOAC Filter was observed on LA testing in controls (n=31) and LA positive (n=37) non-anticoagulated samples. dRVVT and SCT remained positive in respectively 16 and 8% of rivaroxaban and 41 and 18% of apixaban samples. DOAC Filter would be an easy-to-use device allowing FXa inhibitors removal from plasma samples limiting their interference with LA testing in treated patients.